Identification of Rhodococcus erythropolis Promoters Controlled by Alternative Sigma Factors Using In Vivo and In Vitro Systems and Heterologous RNA Polymerase - Blumenstein, Jan; Rädisch, Robert; Štěpánek, Václav; Grulich, Michal; Dostálová, Hana; Pátek, Miroslav (Current microbiology, 2022)
Rhodococcus erythropolis CCM2595 is a bacterial strain, which has been studied for its capability to degrade phenol and other toxic aromatic compounds. Its cell wall contains mycolic acids, which are also an attribute of other bacteria of the Mycolata group, such as Corynebacterium and Mycobacterium species. We suppose that many genes upregulated by phenol stress in R. erythropolis are controlled by the alternative sigma factors of RNA polymerase, which are active in response to the cell envelope or oxidative stress. We developed in vitro and in vivo assays to examine the connection between the stress sigma factors and genes activated by various extreme conditions, e.g., heat, cell surface, and oxidative stress. These assays are based on the procedures of such tests carried out in the related species, Corynebacterium glutamicum. We showed that the R. erythropolis CCM2595 genes frmB1 and frmB2, which encode S-formylglutathione hydrolases (named corynomycolyl transferases in C. glutamicum), are controlled by SigD, just like the homologous genes cmt1 and cmt2 in C. glutamicum. The new protocol of the in vivo and in vitro assays will enable us to classify R. erythropolis promoters according to their connection to sigma factors and to assign the genes to the corresponding sigma regulons. The complex stress responses, such as that induced by phenol, could, thus, be analyzed with respect to the gene regulation by sigma factors.
Keywords: Rhodococcus; Corynebacterium glutamicum; Sigma Factor; Promoter Regions, Genetic; DNA-Directed RNA Polymerases; promotorové oblasti (genetika); sigma faktor; DNA řízené RNA-polymerasy